(untitled) (VERUM: Journal of Scientific Initiation, 2026)
This paper addresses the theme of industrial property, focusing on the study of legal instruments for the protection of industrial property, such as trademarks, patents, geographical indications, and industrial designs. The research problem can be defined as follows: “what are the legal instruments for the protection of industrial property?” In view of this question, the central objective of the research is to define the legal instruments for the protection of industrial property, as well as to understand the general aspects related to such instruments. To achieve the research objective, an analytical methodology was employed, with research based on indirect sources, such as books, scientific articles, and legislation.